Cover Feature: Design and Analysis of the 4‐Anilinoquin(az)oline Kinase Inhibition Profiles of GAK/SLK/STK10 Using Quantitative Structure‐Activity Relationships (ChemMedChem 1/2020). (13th January 2020) - Asquith, Christopher R. M.; Laitinen, Tuomo; Bennett, James M.; Wells, Carrow I.; Elkins, Jonathan M.; Zuercher, William J.; Tizzard, Graham J.; Poso, Antti
Abstract : The cover feature shows the key 4‐anilinoquinoline ligand (6, 7‐dimethoxy‐ N ‐(3, 4, 5‐trimethoxyphenyl)quinolin‐4‐amine) modelled in cyclin G associated kinase (GAK). The image shows a zoomed‐in version of the 3D‐QSAR model that Christopher R. M. Asquith et al. developed for GAK inhibition, as described in their Full Paper. In addition, they developed models for STE20‐like serine/threonine protein kinase (SLK) and serine/threonine protein kinase 10 (STK10), all with the 4‐anilinoquin(az)oline inhibitor scaffold. These models are a basis for further inhibitor development and understanding of wider kinase inhibitor design. More information can be found in the Full Paper by Asquith et al. on page 26 in Issue 1, 2020 (DOI: 10.1002/cmdc.201900521 ). Cover image by Tuomo Laitinen and Christopher Asquith.